ALTERNATIF DESAIN GEDUNG GUESTWING 1 THE RITZ CARLTON HOTTEL DENGAN SISTEM GANDA - Anggi Prasetya I Made; I Putu Ellsa Sarassantika; Cokorda Agung Yujana; I Wayan Gde Erick Triswandan; I Putu Deny Surastika Aditama (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2024)
When planning a tall building structure, the deviation due to lateral forces is very important to be taken into account in the planning of tall building structures. To reduce the amount of deviation in the structure adding by special structural elements, as shear walls. With the shear wall, can increase the stiffness of the building structure and absorb large shear forces along with higher the building structure and lateral force on structure will not fully accepted by frame structure which will result a decrease in deviation. Guestwing 1 The Ritz Carlton Hottel located in South Kuta District, Badung Regency, Bali. This building has a height of 20.2 m consisting of 6 floors. Planning with 2 models: a) SRPMK Existing Modeling, b) Dual System Model. Material specifications and loading are the same, just different in addition of shear walls and reducing the dimensions the building. Based on the results the analysis of the two models, the largest inter-storey deviation value in the existing model X=52.014mm; Y=47.960mm and for the dual system model X=25.614mm; Y=26.026mm. From the results of deviation analysis on both models, can be concluded that with addition of shear walls, there is a decrease in deviation 63.27% in X direction and 68.18% in Y direction. The most significant decrease occurs in dimensions and reinforcement of column K1 from size 350x800mm with 22 D22 reinforcement to column 300x600mm with 18 D22 reinforcement, beam B3 250x450mm for support area 17 D13 and field area 10 D13 to beam 250x400mm with the number of support reinforcement 11 D13, and the number of field reinforcement 7 D13. From the results of this planning can be used as a consideration for the construction of the next building for the use of shear walls in the structure.